Adsorption of heavy metal from landfill leachate by wasted biosolids - Al-Mamun, Abdullah; Alam, Md Zahangir; Nik Mohd, Nik Amirul; Rashid, Shah Samiur (Academic Journals, 2011)
The adsorption capacity of wasted solids that contained dead fungal biomass (Phanerochaete chrysosporium) was studied to remove cadmium, copper, zinc and iron from synthetic water and leachate. The biomass was produced due to the experiments conducted for bioconversion of wastewater for lignin peroxydase production in the laboratory. In the screening experiments, the maximum cadmium (Cd) adsorption from synthetic water was 28.81% at 18 hours. Meanwhile, adsorption of copper (Cu), zinc (Zn) and iron (Fe) reached maximum condition after 5 hours with 41.29%, 58.94%, and 52.03% removal efficiency, respectively. However, the concentration of Cd, Cu and Zn was not detected in the leachate but Fe was found to be in high concentration (184 mg/L) in raw leachate collected from a municipal landfill site. Therefore, the effects of biomass dosage, contact time, pH and agitation speed were observed for optimal adsorption of iron from leachate. Optimum removal of iron from leachate was 45.56% in every 1 L of leachate after 1/50 dilutions. The optimized biomass dosage, contact time, pH and agitation speed were 750 mg/L, 4 hours, pH 5, and 150 rpm, respectively. The results of this project indicated that the biomass generated from the laboratory experiments could be used, before discarding, to remove iron from leachate which is one of the main problems at the landfill sites. However, further studies are required to determine the appropriate doses and overall processes of treatment method.